Architucture, need and services. Warehouses, markets, hypermarkets, fairs and shopping centers - Chumpitaz Mellarez, Felipe (2023)
Architecture, through urban planning, is in a position to develop urban planning proposals. They, taking into account the participation of commercial buildings, are expected to contribute to the development of the socio-cultural dynamics of a community and its economic progress simultaneously. In addition, they are intended to strengthen the concept of citizenship as the right to free and democratic use of public space in accordance with private property.